2021
DOI: 10.3390/cancers13061368
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Oral- and Sero- Positivity in Fanconi Anemia

Abstract: High-risk human papillomavirus (HPV) is prevalent and known to cause 5% of all cancers worldwide. The rare, cancer prone Fanconi anemia (FA) population is characterized by a predisposition to both head and neck squamous cell carcinomas and gynecological cancers, but the role of HPV in these cancers remains unclear. Prompted by a patient-family advocacy organization, oral HPV and HPV serological studies were simultaneously undertaken. Oral DNA samples from 201 individuals with FA, 303 unaffected family members,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…FARG was shown to be differentially expressed and tended to concentrate on similar functional pathways in various cancers ( Figures 1B,K ). FARGs play an important role in DNA repair, as well as in protecting the human genome during genome integration of viruses such as HPV ( Ruiz-Torres et al, 2021 ; Sauter et al, 2021 ). Based on this information, we found that some sites in FARGs were HPV integration hot-spots, and expression of FARGs was moderately or strongly correlated with the expression of the genes where the integration hot-spots were located.…”
Section: Discussionmentioning
confidence: 99%
“…FARG was shown to be differentially expressed and tended to concentrate on similar functional pathways in various cancers ( Figures 1B,K ). FARGs play an important role in DNA repair, as well as in protecting the human genome during genome integration of viruses such as HPV ( Ruiz-Torres et al, 2021 ; Sauter et al, 2021 ). Based on this information, we found that some sites in FARGs were HPV integration hot-spots, and expression of FARGs was moderately or strongly correlated with the expression of the genes where the integration hot-spots were located.…”
Section: Discussionmentioning
confidence: 99%